Optimalisasi Strategi Penggunaan Media Sosial Dalam Menciptakan Customer Engagement Pada Usaha Kecil Dan Menengah - Tito Siswanto; Suparman Suparman; Aldi Fathurrahman (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2020)
Various companies continue to innovate and adapt to survive in the competition. The development of technology and information, easy internet access, and the industrial revolution 4.0 are entering the business world to quickly respond to everything. In addition, the use of social media with internet support makes marketing activities attractive, because consumer interaction in the era of social media is important things in marketing activities. Research was conducted to see promotional strategies using social media and to provide recommendations for priority promotion strategies using social media in creating customer engagement. This study uses the Analitycal Hierarchy Process (AHP) method to see strategic priorities and qualitative analysis to explore. From this research, it is known that in creating customer engagement, the target that must be prioritized is interaction, because the interaction dimension is known to be more dominant than other targets. In order to achieve these targets so as to create customer engagement through the use of social media, the strategic priority that can be carried out by each company is the use of an influence model. In addition, the use of social media is also required to be creative and innovative in order to influence consumers through a variety of content created, such as videos, photos and text messages. Furthermore, the important findings of the research are presented in full in this paper.